2017
DOI: 10.3390/su9071102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Video and 3D Scenario Visualisation to Rate Vegetation Screens for Integrating Buildings into the Landscape

Abstract: Human actions in the natural environment create a visual impact. The main objective of this study was to examine the acceptance of vegetation screens for integrating buildings into the landscape using new techniques of visualization in three dimensions (3D), videos and public participation. The status quo of two study areas representative of the Mediterranean climate in Spain (one inland and one coastal) was modelled, placing vegetation screens around a building typical of the area and varying the density, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This shows that respondents did not visually prefer this type of arrangement to an irregular or dispersed arrangement. Similar results were obtained by Garrido et al [39], although these authors did not quantify the percentage of vegetation used or measure its impact.…”
Section: Rating Of Vegetation Screening (Test Images a B C And D)supporting
confidence: 83%
See 2 more Smart Citations
“…This shows that respondents did not visually prefer this type of arrangement to an irregular or dispersed arrangement. Similar results were obtained by Garrido et al [39], although these authors did not quantify the percentage of vegetation used or measure its impact.…”
Section: Rating Of Vegetation Screening (Test Images a B C And D)supporting
confidence: 83%
“…Both graphics also show a nonlinear trend in respondents' answers. Other authors reported that 40-50% shifts in visual stimuli [7,20,39] become appreciable for observers.…”
Section: Rating Of Vegetation Screening (Test Images a B C And D)mentioning
confidence: 96%
See 1 more Smart Citation
“…Smardon 1988Smardon , 2016Grahn and Stigsdotter 2010) that included assessments of shape, color, scale and texture. With the increasing sophistication of computing power, however, visualizations have progressed to 2D representations of space using GIS (Bishop 2003;Van Herzele and Wiedemann 2003;Pettit et al 2006;Ives et al 2017), 3D, and virtual reality representations (Bishop 2003;Pettit et al 2006;Fisher-Gewirtzman 2012;Yokoya et al 2014;Portman et al 2015;Li et al 2015;Velarde et al 2017;Echevarria Sanchez et al 2017). Mixed method approaches using questionnaires, semi-structured surveys, indicators, and multivariate analyses such as analytic hierarchy process (AHP) and principal component analysis also are being applied with increasing frequency (Van Herzele and Wiedemann 2003;Bulut and Yilmaz 2009;Hoyle et al 2017;Meri and Lian 2017).…”
Section: Visioning Urban Landscape and Greenmentioning
confidence: 99%
“…Therefore, there is a global concerning considering Sustainable development regional strategies for territorial growth [8,9,10,11]. In fact, this is one of the biggest challenges of regional planning nowadays [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%